Comparative Performance of In-House and Commercially Available ELISA Kits for the Detection of Antibody Against Newcastle Disease Virus Vaccine (Progressive Agriculture, 2013)
An In-house Indirect enzyme-linked immunosorbent assay (ELISA) was developed for the detection of serum antibody titre against Newcastle disease virus (NDV) and was compared its sensitivity and specificity with the commercially available NDV antibody detection ELISA kit (Biocheck®, USA). The reference NDV was purified by centrifugation, ultracentrifugation and by sucrose density gradient ultracentrifugation. This purified NDV was used for coating of 96-well flat bottomed microtitre plate and to raise hyperimmune sera (known) in Fayoumi chickens. In the standardization test, the antigen dilution of 10-6 and the serum dilution of 10-3 were considered to be optimum for the present ELISA system. The correlation regression analysis was performed to construct a standard curve equation where a good positive correlation was observed (r = 0.912, n = 8, P